ASME 2009 7th International Conference on Nanochannels, Microchannels and Minichannels 2009
DOI: 10.1115/icnmm2009-82121
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Investigation of Non-Uniform Heating on Flow Boiling Instabilities in a Microchannels Based Heat Sink

Abstract: Two-phase flow boiling in microchannels is one of the most promising cooling technologies able to cope with high heat fluxes generated by the next generation of central processor units (CPU). If flow boiling is to be used as a thermal management method for high heat flux electronics it is necessary to understand the behaviour of a non-uniform heat distribution, which is typically the case observed in a real operating CPU. The work presented is an experimental study of two-phase boiling in a multi-channel silic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 9 publications
(9 reference statements)
0
1
0
Order By: Relevance
“…Past experimental efforts have studied the effects of non-uniform microchannel heating on flow boiling instabilities [17], pressure drop, and maximum wall temperatures [18][19][20]. It was found that hotspots near the inlet created a large transverse temperature variation across the heat sink due to nonuniform fluid distribution.…”
Section: Introductionmentioning
confidence: 99%
“…Past experimental efforts have studied the effects of non-uniform microchannel heating on flow boiling instabilities [17], pressure drop, and maximum wall temperatures [18][19][20]. It was found that hotspots near the inlet created a large transverse temperature variation across the heat sink due to nonuniform fluid distribution.…”
Section: Introductionmentioning
confidence: 99%